Modern Computer Architecture and Organization Learn X86, ARM, and RISC-V Architectures and the Design of Smartphones, PCs, and Cloud Servers. - Ledin, Jim (Packt Publishing, Limited, 2020)
A no-nonsense, practical guide to help you learn the current and future processor and computer architectures that will enable you to design computer systems and develop better software applications across a variety of domains.